2003
DOI: 10.1177/106689690301100314
|View full text |Cite
|
Sign up to set email alerts
|

Oncocytic Angiomyolipoma of the Kidney: A Case Report

Abstract: We describe a case of oncocytic angiomyolipoma composed of polygonal eosinophilic cells, that shares many features with renal oncocytoma. It was composed of alveolar structures, with accumulation of foamy histiocyte-like cells surrounding large globules of acellular, nonfibrillary, densely eosinophilic basal membrane-like substance. Immunohistochemically, there was focal reactivity for HMB45 and negativity for the epithelial markers. Oncocytic angiomyolipoma lacks the atypical features of the recently describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Moreover, 1 group 44 has reported TFEB IHC labeling in PEComa family lesions, although this has not been our experience, and we have subsequently found that all PEComas tested so far lack TFEB gene rearrangements. Illustrating the diagnostic difficulty, the provided images of a distinctive renal neoplasm reported as “oncocytic angiomyolipoma” in 2003 45 appear to be quite consistent with a t(6;11) RCC. Moreover, there are also at least 2 t(6;l 1) RCCs reported in the literature in which epithelioid angiomyolipoma was the initial favored diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 1 group 44 has reported TFEB IHC labeling in PEComa family lesions, although this has not been our experience, and we have subsequently found that all PEComas tested so far lack TFEB gene rearrangements. Illustrating the diagnostic difficulty, the provided images of a distinctive renal neoplasm reported as “oncocytic angiomyolipoma” in 2003 45 appear to be quite consistent with a t(6;11) RCC. Moreover, there are also at least 2 t(6;l 1) RCCs reported in the literature in which epithelioid angiomyolipoma was the initial favored diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The review of the literature on the FNA diagnosis of epithelioid AMLs shows that their unusual cytologic features overlapping with those of HCCs 18 and renal cell carcinomas 41, 42 may lead to a misdiagnosis. On FNA smears or touch imprint preparations, epithelioid renal, 27, 41–43 peritoneal, 44 or hepatic 29, 31 AMLs show similar findings. Typically, little or no fat and no thick‐walled blood vessels are seen in smears or cell block preparations and the cytology is characterized by the presence of numerous monomorphic or pleomorphic epithelioid cells and naked nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelioid angiomyolipoma (EAML) of the kidney is a relatively newly described renal neoplasm that is closely related to the more common classic angiomyolipoma (AML) of the kidney and perivascular epithelioid cell neoplasm of extrarenal sites 1–4 . EAML is characterized by sheets of epithelioid cells displaying varying degrees of nuclear atypia often mimicking renal epithelial neoplasms 5–45 . In contrast to the classic AML, EAML may be associated with an adverse clinical course.…”
Section: Introductionmentioning
confidence: 99%